Central venous catheters retention in a patient with mitral valve replacement: a case report - Ngurah Dwiky Abadi Resta; I Nyoman Semadi; I Komang Adhi Parama Harta; I Wayan Sudarma; Ketut Putu Yasa (Journal of Indonesia Vascular Access, 2021)
Background: Retention of central venous catheters (CVC) is one complication that may occur when open-heart surgery is performed (such as mitral valve replacement). In this case report, we describe case retention of CVC in a patient with Mitral Valve Replacement (MVR) related to sutured of Superior Vena Cava (SVC) wall on cannulation site. Case Presentation:  A 15-year-old boy was admitted to Sanglah Hospital with a history of Heart failure with severe regurgitation of the mitral valve, severe tricuspid regurgitation, and left ventricular dysfunction due to rheumatic heart disease. Mitral valve replacement, tricuspid valve repair and left atrial reduction was performed. After five days of postoperative observation, the CVC could be removed. However, there is resistance when removing the catheter. After diagnostic examination, it was found that the CVC was sutured to the superior vena cava wall. The patient was then scheduled for a redo sternotomy to evacuate the CVC. The patient was discharged seven days after redo sternotomy was performed without any further postoperative complications. Conclusions: Retention of CVC during open-heart surgery is one complication that increases the risk for morbidity or mortality to the patient after heart surgery.